Struktur Modul Hasil Bagi dari Modul Dedekind - Hanni Garminia; Pudji Astuti; Irawati Irawati (Institut Teknologi Bandung, 2008)
It is well known that the quotient ring of a Dedekind prime ring is a Dedekind prime ring. In this article we generalize the property of Dedekind ring to a module over a commutative ring. Particularly we show that the quotient module of a Dedekind module is a Dedekind module.